Hollow nickel alloy breathable porous material and preparation method thereof

The hollow nickel alloy breathable porous materials are prepared through defatted cotton carbonization and nickel plating processes, which solves the problems of high density and poor permeability of existing nickel alloy fiber breathable materials in high temperature environments, and achieves the effect of low density and good permeability, which is suitable for the aerospace field.

CN119553191APending Publication Date: 2025-03-04BEIJING INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411789029.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing nickel alloy fiber breathable materials have problems such as high density, insufficient permeability and insufficient strength in high temperature environments, which are difficult to meet the demanding needs of the aerospace field.

Method used

Through defatted cotton carbonization, nickel plating, dry blanking, wet hydrogen sintering and solid phase impregnation, hollow nickel alloy breathable porous materials were prepared, achieving low density and good permeability.

Benefits of technology

While ensuring strength, this material has lower density and better permeability. It is suitable for high-temperature sweat-induced cooling applications in aerospace, expanding the application range of traditional metal breathable materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553191A_ABST
    Figure CN119553191A_ABST
Patent Text Reader

Abstract

The invention relates to a hollow nickel alloy breathable porous material and a preparation method thereof, and belongs to the technical field of breathable sweating metal materials. The method comprises the following steps: drying absorbent cotton, and carbonizing; then carrying out nickel plating treatment on the absorbent cotton carbonized fibers; and then carrying out dry-process blank making, wet hydrogen sintering and solid-phase infiltration, and finally rolling to obtain the hollow nickel alloy breathable porous material. The material has low density, has good permeability while ensuring the strength, and has good application prospects in the field of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hollow nickel alloy breathable porous material and a preparation method thereof, belonging to the technical field of breathable and sweat-generating metal materials. Background Art

[0002] Metal fiber breathable materials prepared by sintering metal fibers are widely used in the sealing gaskets of aircraft engines and gas turbines. They can withstand heat temperatures as high as 1200°C and can effectively reduce leakage between compressors and turbines. At the same time, this metal fiber breathable material is widely used in active cooling parts such as the ends of high-speed aircraft due to its excellent high-pressure permeability, light weight, high strength and many other advantages, effectively reducing aerodynamic heating and achieving excellent thermal protection effects. Metal fiber breathable materials are also widely used in many fields such as high-temperature environment filtration, multi-spectral noise reduction and shielding, and play an extremely important role in national economic construction.

[0003] At present, nickel alloy fiber breathable materials have outstanding heat resistance and are the most widely used type of metal fiber breathable materials. They are mostly prepared by fiber spinning and then sintering. In recent years, Professor Chen Weiwei's research group has developed a new type of nickel alloy hollow fiber sintered felt (Wei X, Zhang Y, Ma B, et al. An investigation of hollow NiCrAl metal fiber porous material for high-temperature sealing [J]. Journal of Alloys and Compounds, 2023, 947: 169493.), which uses short-cut carbon fiber nickel plating, wet hydrogen sintering, alloy infiltration and other processes. It has been applied to the field of high-temperature dynamic sealing. The traditional short-cut PAN-based carbon fiber is mainly used to prepare nickel alloy felt. However, this kind of carbon fiber has a smooth surface, uniform thickness, and straight fibers. The surface is coated with a nickel layer and has many pores after sintering. The strength is insufficient and it is difficult to meet the needs of more demanding application environments. Zhao Shaoyang et al. prepared nickel-based breathable and sweating materials by cold pressing-vacuum sintering method (Zhao Shaoyang, Yang Chong, Zhang Shuai, et al. Research on the preparation process of nickel-based high-temperature alloy porous sweating materials [J]. Aviation Manufacturing Technology, 2023, 66(18): 74-78.), but the material is prepared from nickel-based alloy powder, with high density, high sintering temperature, long sintering time, many closed pores, and the permeability of the material is not good enough. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a hollow nickel alloy breathable porous material and a preparation method thereof. The material has a relatively low density, good permeability while ensuring strength, and has good application prospects in the aerospace field.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows.

[0006] A method for preparing a hollow nickel alloy breathable porous material, the method steps comprising:

[0007] (1) Carbonization of absorbent cotton: The absorbent cotton is dried and then carbonized at a temperature of 600 to 1200° C. for a holding time of 4 to 8 hours to obtain curled and mutually entangled carbonized absorbent cotton fibers;

[0008] (2) Nickel plating: The absorbent cotton carbonized fiber is subjected to nickel plating treatment to obtain a nickel-plated absorbent cotton carbonized fiber with a coating thickness of 1 to 3 μm;

[0009] (3) Dry process blanking: Physically vibrate the carbonized fibers of nickel-plated absorbent cotton to mix and distribute them evenly to obtain a blank;

[0010] (4) Wet hydrogen sintering: placing the green body into a wet hydrogen sintering furnace, sintering at 750-1100° C. for 8-12 hours in a mixed atmosphere of hydrogen and water vapor, to obtain a hollow porous nickel matrix composed of hollow nickel fibers;

[0011] (5) solid phase infiltration: placing the hollow porous nickel substrate into an infiltration furnace and infiltrating it with Cr or Al to obtain a hollow nickel alloy porous material;

[0012] (6) Rolling: The nickel alloy porous material is subjected to multiple rolling processes to obtain a hollow nickel alloy breathable porous material.

[0013] Preferably, in step (1), the carbonization temperature is 900-1000° C. and the insulation time is 5-6 hours.

[0014] Preferably, in step (1), the carbonized cotton fibers have a length of 0.3 to 1.5 mm and a diameter of 1 to 10 μm.

[0015] Preferably, in step (2), during nickel plating, the plating solution is a Watt solution, the nickel plating voltage is 5 to 20 V, the current is 30 to 60 A, and the time is 1 to 5 hours.

[0016] Preferably, in step (4), the hydrogen flow rate is 2 to 5 L / min, and the water vapor flow rate is 1 to 3 L / min.

[0017] Preferably, in step (4), the density of the porous nickel substrate is 0.8 to 1 g / cm 3 .

[0018] Preferably, in step (5), the impregnation material is a mixture of elemental metal powder and NH4Cl powder in a mass ratio of 5 to 10:1, and the mass ratio of the hollow porous nickel matrix to the impregnation material is 2 to 5:1.

[0019] Preferably, in step (5), the impregnation temperature is 1000-1200° C., and the impregnation time is 8-14 hours.

[0020] Preferably, in step (6), the rolling pressure per pass is 0.5 to 2 mm, and the final density after rolling is 3 to 7 g / cm 3 .

[0021] A hollow nickel alloy breathable porous material is prepared by the above method.

[0022] Beneficial Effects

[0023] (1) In the present invention, the carbonized fibers of the absorbent cotton produced after high-temperature carbonization have a spiral surface, a larger specific surface area, a disorderly and curly shape, and the fibers are entangled with each other in three-dimensional space, which is conducive to sintering to form a porous material with higher strength.

[0024] (2) In the present invention, the carbonized absorbent cotton fiber can be electroplated to form a coating layer with a thickness of 1 to 3 μm, which is thicker than the nickel plating thickness of conventional carbon fibers such as adhesive fibers, thus providing an advantage for further sintering into a nickel blank.

[0025] (3) In the present invention, dry-process blank making is adopted, which avoids the problem of uneven mixing caused by fiber sedimentation or floating during wet-process blank making, and also avoids the damage to the fibers caused by blank making methods such as ball milling, and can effectively ensure the uniform distribution of nickel-plated fibers, thereby ensuring the blank making effect.

[0026] (4) In the present invention, wet hydrogen sintering is adopted to remove the carbon core while retaining the complete hollow fiber structure. The prepared nickel-chromium breathable material has lower density and better permeability than the traditional nickel-chromium porous material.

[0027] (5) The present invention obtains a hollow nickel alloy breathable material by a method of nickel plating-wet hydrogen sintering-solid phase infiltration. Compared with the porous material prepared from traditional nickel alloy powder, the hollow nickel alloy breathable material has higher specific strength and air permeability. This provides a new idea for the application of metal breathable materials in high-temperature sweating cooling in aerospace, and expands the application scope of traditional metal breathable materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the permeability result of the hollow NiCr breathable porous material described in Example 1.

[0029] Figure 2 These are scanning electron microscope (SEM) images of the materials obtained at different stages in Example 2, (a) carbonized cotton fiber, (b) nickel-plated carbonized cotton fiber, (c) hollow porous nickel matrix, and (d) hollow nickel NiCr breathable porous material.

[0030] Figure 3 This is the tensile stress-strain curve of the hollow NiCr breathable porous material described in Example 3. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to specific examples. The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0032] Example 1

[0033] (1) 200 g of cotton wool was dried and placed in a muffle furnace, heated to 600 °C, and maintained for 8 h to obtain carbonized cotton wool fibers.

[0034] (2) The absorbent cotton carbonized fiber is placed in a nickel plating device for electroplating, wherein the electrolyte composition is 300 g / L nickel sulfate, 30-35 g / L nickel chloride, and 30-35 g / L boric acid, and the electroplating voltage is adjusted to 5 V, the current is 30 A, and the electroplating is performed for 5 hours. After the nickel plating is completed, the carbonized absorbent cotton fiber is washed and dried to obtain the nickel-plated absorbent cotton carbonized fiber.

[0035] (3) 150 g of the nickel-plated absorbent cotton carbonized fiber was placed in a mold with a length of 120 mm, a width of 70 mm, and a height of 10 mm, and the mold was formed uniformly by physical vibration to obtain a green body.

[0036] (4) The green body was placed in a wet hydrogen sintering furnace at a sintering temperature of 750°C for 12 hours, a hydrogen flow rate of 2 L / min, and a water vapor flow rate of 1 L / min to obtain a hollow porous nickel matrix composed of hollow nickel fibers with a density of 0.8 g / cm 3 .

[0037] (5) Add Cr powder and NH4Cl powder in a mass ratio of 7:1 into a ball mill, mix them evenly by ball milling to form an impregnation mixture; put the hollow porous nickel substrate into an infiltration furnace, and put it into an infiltration bag with the infiltration mixture in a mass ratio of 3:1, and then put it into a tubular furnace for infiltration under an argon protective atmosphere. The infiltration temperature is 1000°C and the time is 14 hours to obtain a hollow NiCr porous material.

[0038] (6) The hollow NiCr porous material is rolled through a rolling mill, with a reduction of 0.5 mm per pass to obtain a density of 3 g / cm 3 Hollow NiCr breathable porous material.

[0039] After testing, the room temperature tensile strength of the hollow NiCr breathable porous material prepared in Example 1 is 80 MPa; Figure 1 As shown, the material permeability is 2.1×10 -12 m 2 .

[0040] Example 2

[0041] (1) 200 g of cotton wool was dried and placed in a muffle furnace, heated to 900 °C and maintained for 6 h to obtain carbonized cotton wool. The SEM test results are shown in Figure 2 As shown in (a).

[0042] (2) The absorbent cotton carbonized fiber is placed in a nickel plating device for electroplating. The electrolyte composition is 300 g / L nickel sulfate, 30-35 g / L nickel chloride, and 30-35 g / L boric acid. The electroplating voltage is adjusted to 10 V, the current is 40 A, and the electroplating is performed for 3 hours. After the nickel plating is completed, the carbonized absorbent cotton fiber is washed and dried to obtain a nickel-plated absorbent cotton carbonized fiber. The SEM test results are as follows: Figure 2 As shown in (b).

[0043] (3) 150 g of the nickel-plated absorbent cotton carbonized fiber was placed in a mold with a length of 120 mm, a width of 70 mm, and a height of 10 mm, and the mold was formed uniformly by physical vibration to obtain a green body.

[0044] (4) The green body was placed in a wet hydrogen sintering furnace at a sintering temperature of 900°C for 10 hours, a hydrogen flow rate of 3 L / min, and a water vapor flow rate of 2 L / min to obtain a hollow porous nickel matrix composed of hollow nickel fibers with a density of 0.9 g / cm 3 , the SEM test results are as follows Figure 2 As shown in (c).

[0045] (5) Cr powder and NH4Cl powder were added to a ball mill at a mass ratio of 7:1, and mixed evenly by ball milling to form an impregnation mixture; the hollow porous nickel substrate was placed in an infiltration furnace, and loaded into an infiltration bag with the infiltration mixture at a mass ratio of 3:1, and then placed in a tubular furnace for infiltration under an argon protective atmosphere. The infiltration temperature was 1100°C and the time was 11 hours to obtain a hollow NiCr porous material, and its SEM test results are shown as follows: Figure 2 As shown in (d).

[0046] (6) The hollow NiCr porous material is rolled through a rolling mill, with a reduction of 1 mm per pass to obtain a density of 5 g / cm 3 Hollow NiCr breathable porous material.

[0047] After testing, the room temperature tensile strength of the hollow NiCr breathable porous material prepared in Example 1 is 182 MPa, and the permeability of the material is 6.8×10 -13 m 2 .

[0048] Example 3

[0049] (1) 200 g of cotton wool was dried and placed in a muffle furnace, heated to 1200 °C and maintained for 4 h to obtain carbonized cotton wool fibers.

[0050] (2) The absorbent cotton carbonized fiber is placed in a nickel plating device for electroplating, wherein the electrolyte composition is 300 g / L nickel sulfate, 30-35 g / L nickel chloride, and 30-35 g / L boric acid, and the electroplating voltage is adjusted to 20 V, the current is 60 A, and the electroplating is performed for 1 hour. After the nickel plating is completed, the carbonized absorbent cotton fiber is washed and dried to obtain the nickel-plated absorbent cotton carbonized fiber.

[0051] (3) 150 g of the nickel-plated absorbent cotton carbonized fiber was placed in a mold with a length of 120 mm, a width of 70 mm, and a height of 10 mm, and the mold was formed uniformly by physical vibration to obtain a green body.

[0052] (4) The green body was placed in a wet hydrogen sintering furnace at a sintering temperature of 1100° C. for 8 hours, a hydrogen flow rate of 5 L / min, and a water vapor flow rate of 3 L / min to obtain a hollow porous nickel matrix composed of hollow nickel fibers with a density of 1 g / cm 3 .

[0053] (5) Add Cr powder and NH4Cl powder in a ball mill at a mass ratio of 7:1, mix them evenly by ball milling to form an infiltration mixture; put the hollow porous nickel substrate into an infiltration furnace and load it into an infiltration bag with the infiltration mixture in a mass ratio of 3:1, and then put it into a tubular furnace for infiltration under an argon protective atmosphere at a temperature of 1200°C for 8 hours to obtain a hollow NiCr porous material.

[0054] (6) The hollow NiCr porous material is rolled through a rolling mill, with each pass reducing 2 mm to obtain a density of 7 g / cm 3 Hollow NiCr breathable porous material.

[0055] After testing, the room temperature tensile strength of the hollow NiCr breathable porous material prepared in Example 1 is 309 MPa. Figure 3 As shown; the permeability of the material is 3.5×10 -13 m 2 .

[0056] Comparative Example 1

[0057] In step (1) of this comparative example, the carbonization temperature is 600° C., the holding time is 2 hours, and the rest is the same as in Example 1.

[0058] The room temperature tensile strength of the material prepared in Comparative Example 1 was 69 MPa and the permeability was 1.1×10 -13 m 2 .

[0059] Comparative Example 2

[0060] In step (1) of this comparative example, the carbonization temperature is 1200° C., the holding time is 10 hours, and the rest is the same as in Example 1.

[0061] The room temperature tensile strength of the material prepared in Comparative Example 1 was 124 MPa and the permeability was 5.6×10 -14 m 2 .

[0062] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing a hollow nickel alloy breathable porous material, characterized in that: The method steps include: (1) Carbonization of absorbent cotton: The absorbent cotton is dried and then carbonized at a temperature of 600 to 1200° C. for a holding time of 4 to 8 hours to obtain curled and mutually entangled carbonized absorbent cotton fibers; (2) Nickel plating: The absorbent cotton carbonized fiber is subjected to nickel plating treatment to obtain a nickel-plated absorbent cotton carbonized fiber with a coating thickness of 1 to 3 μm; (3) Dry process blanking: Physically vibrate the carbonized fibers of nickel-plated absorbent cotton to mix and distribute them evenly to obtain a blank; (4) Wet hydrogen sintering: placing the green body into a wet hydrogen sintering furnace, sintering at 750-1100° C. for 8-12 hours in a mixed atmosphere of hydrogen and water vapor, to obtain a hollow porous nickel matrix composed of hollow nickel fibers; (5) solid phase infiltration: placing the hollow porous nickel substrate into an infiltration furnace and infiltrating it with Cr or Al to obtain a hollow nickel alloy porous material; (6) Rolling: The nickel alloy porous material is subjected to multiple rolling processes to obtain a hollow nickel alloy breathable porous material.

2. The method for preparing a hollow nickel alloy breathable porous material according to claim 1, characterized in that: In step (1), the carbonization temperature is 900-1000° C. and the insulation time is 5-6 hours.

3. A method for preparing a hollow nickel alloy breathable porous material as claimed in claim 1 or 2, characterized in that: In step (1), the carbonized cotton fibers have a length of 0.3 to 1.5 mm and a diameter of 1 to 10 μm.

4. The method for preparing a hollow nickel alloy breathable porous material according to claim 1, characterized in that: In step (2), during nickel plating, the plating solution is a Watt solution, the nickel plating voltage is 5 to 20 V, the current is 30 to 60 A, and the time is 1 to 5 hours.

5. The method for preparing a hollow nickel alloy breathable porous material according to claim 1, characterized in that: In step (4), the hydrogen flow rate is 2 to 5 L / min, and the water vapor flow rate is 1 to 3 L / min.

6. The method for preparing a hollow nickel alloy breathable porous material according to claim 1 or 5, characterized in that: In step (4), the density of the porous nickel substrate is 0.8 to 1 g / cm 3 .

7. The method for preparing a hollow nickel alloy breathable porous material according to claim 1, characterized in that: In step (5), the impregnation material is a mixture of elemental metal powder and NH4Cl powder in a mass ratio of 5 to 10:1, and the mass ratio of the hollow porous nickel matrix to the impregnation material is 2 to 5:

1.

8. The method for preparing a hollow nickel alloy breathable porous material according to claim 1 or 7, characterized in that: In step (5), the impregnation temperature is 1000-1200° C., and the impregnation time is 8-14 hours.

9. The method for preparing a hollow nickel alloy breathable porous material according to claim 1, characterized in that: In step (6), the rolling pressure per pass is 0.5 to 2 mm, and the final density of the rolled product is 3 to 7 g / cm 3 .

10. A hollow nickel alloy breathable porous material, characterized in that: It is prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Lightweight ablation-resistant metal-based thermal protection material and preparation method thereof

    CN120485669A